2014
DOI: 10.1016/j.celrep.2013.12.013
|View full text |Cite
|
Sign up to set email alerts
|

RNAi Factors Are Present and Active in Human Cell Nuclei

Abstract: Summary RNAi is widely appreciated as a powerful regulator of mRNA translation in the cytoplasm of mammalian cells. However, the presence and activity of RNAi factors in the mammalian nucleus has been the subject of considerable debate. Here we show that Argonaute-2 (Ago2) and RNAi factors Dicer, TRBP and TRNC6A/GW182 are in the human nucleus and associate together in multi-protein complexes. Small RNAs can silence nuclear RNA and guide site-specific cleavage of the targeted RNA, demonstrating that RNAi can fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
368
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(396 citation statements)
references
References 58 publications
22
368
0
6
Order By: Relevance
“…The latter constitutes evidence of a nuclear PTGS pathway ( Figure 1C). Indeed, increasing evidence supports a functional nuclear PTGS pathway, with a recent study demonstrating not only the presence of PTGS related proteins in the nucleus of mammalian cells, but an active AGO-2-RISC complex able to efficiently cleave two nuclear lncRNAs, Malat1 and Neat1 [101] . These studies add to previous evidence indicating the existence of a nuclear RNAi pathway and suggest that PTGS and TGS may be closely related.…”
Section: Ptgsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter constitutes evidence of a nuclear PTGS pathway ( Figure 1C). Indeed, increasing evidence supports a functional nuclear PTGS pathway, with a recent study demonstrating not only the presence of PTGS related proteins in the nucleus of mammalian cells, but an active AGO-2-RISC complex able to efficiently cleave two nuclear lncRNAs, Malat1 and Neat1 [101] . These studies add to previous evidence indicating the existence of a nuclear RNAi pathway and suggest that PTGS and TGS may be closely related.…”
Section: Ptgsmentioning
confidence: 99%
“…Recent evidence suggests that it may be also triggered by sncRNAs that target the 3' termini of genes [58,106] . While increasing evidence suggests a role for AGO-2 in nuclear gene silencing [100] , it seems to be predominantly through a nuclear PTGS that involves RNA cleavage [101] , with only few described exceptions [107] . There is also evidence of RNA-induced nuclear silencing without heterochromatin formation, involving both AGO1 and AGO2 [108] , and there seems to be various RNA-directed nuclear-pathways that control transcription at different stages [109] .…”
Section: Tgsmentioning
confidence: 99%
“…Although processing of Dicer's substrates occurs in the cytoplasm of mammalian cells, several reports suggest that Dicer may also have additional roles in the nucleus. [24][25][26][27] In support of a nuclear function of Dicer, the C-terminal dsRBD of human Dicer was recently shown to harbor an atypical nuclear localization signal (NLS), composed of a cluster of positively charged residues on the surface of the folded dsRBD (Fig. 1B).…”
Section: Dsrbds and Nuclear Importmentioning
confidence: 99%
“…Recent work has indicated that human AGO proteins can regulate splicing through modulating chromatin structure (9,10) and can promote gene repression in cis by localizing to nascent tRNA (11). Thus, RNAi-mediated control of gene expression exists also in vertebrate cells but functions in mechanisms distinct from those within the cytoplasm (12,13). Despite these reports demonstrating a role for RNAi in regulating the chromatin structure of vertebrates, similar studies have shown that the loss of the RNAi machinery impacts chromatin structure indirectly through miRNA biogenesis and post-transcriptional gene regulation (14).…”
mentioning
confidence: 99%